Ethical implementation of mitochondrial donation in Australia. (16th August 2022) - Koplin, Julian; Lestrell, Esther; Mills, Catherine; Degeling, Chris; Kneebone, Ezra; Ludlow, Karinne; Newson, Ainsley; Sparrow, Robert; Sutton, Liz; Warren, Narelle
Abstract : Australia has recently legalised mitochondrial donation. However, key ethical and legal issues still need to be addressed. This paper maps the relevant issues and offers some suggestions for how they ought to be resolved.